Comparative Analysis of Terahertz Microstrip Patch Antenna with Single SRR and a Metasurface at the Ground Plane for the Medical Applications - Singh K.; Dhayal M.; Dwivedi S. (My University, 2025)
This research includes a comparative study of two ground-plane-structure-variant microstrip patch antennas. The THz frequency band is used by both antennas. The medical sector has taken interest in terahertz (THz=1012 Hz) technology because of its non-invasive and non-ionizing qualities, as it lies between microwave and infrared in the electromagnetic spectrum. In this paper, the design of both antennas has been discussed. Radiation patterns, gain, efficiency, and directivity, as well as the reflection coefficient and VSWR, have all been analyzed and compared. Both antennas are simulated in the frequency range of 0.1 THz to 3 THz, which is suitable for various biomedical applications. Both the microstrip patch antennas are designed and analyzed using CST Microwave Studio. © 2023 IEEE.